Hydrocarbon fluid evolution and accumulation process in ultradeep reservoirs of the northern Fuman Oilfield, Tarim Basin - Wang, Rujun; Zhang, Yingtao; Chen, Fangfang; Li, Mengqin; Wen, Zhigang; Luo, Xiao; Ding, Zhiwen; Li, Bing; Xue, Yifan (Frontiers in Earth Science, 2024)
Marine deep Ordovician reservoirs are significantly controlled by strike-slip fault zones, which govern reservoir fluid evolution during various activity periods. Such fluid evolution elucidates the process underpinning ultra-deep oil and gas accumulation and delineates the pivotal role of strike-slip fault zones in hydrocarbon aggregation. This method can improve the understanding of the mechanism of hydrocarbon accumulation in deep to ultradeep carbonate rocks. The findings indicate that the Ordovician reservoirs in the northern thrust fault zone of the Fuman Oilfield predominantly exhibit two stages of calcite vein formation. The distribution patterns of rare earth elements and Sr isotope characteristics suggest that both stages of vein formation were sourced from Middle to Lower Ordovician marine strata, with no evidence of oxidizing fluid infiltration. This indicates that late-stage oil and gas charging in deep-ultradeep formations has good sealing properties. In these calcite veins, early-, middle-, and late-stage fluid inclusions were primarily entrapped. By examining the development of primary oil inclusions and combining the U‒Pb isotope data of host minerals, this study confirms the occurrence of three stages of oil and gas charging in the deep Ordovician strata of the northern thrust fault zone in the Fuman Oilfield. These stages correspond to approximately 459 ± 7.2 Ma (mid-Caledonian), 348 ± 18 Ma (early Permian), and 268 Ma (late Permian). The key accumulation period of oil and gas reservoirs in the study area is the middle and late Caledonian, and there is a good correspondence between oil and gas charging and fault activity.